2021
DOI: 10.1007/s40271-021-00520-4
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Discrete Choice Experiments in Oncology Treatments

Abstract: Background As the number and type of cancer treatments available rises and patients live with the consequences of their disease and treatments for longer, understanding preferences for cancer care can help inform decisions about optimal treatment development, access, and care provision. Discrete choice experiments (DCEs) are commonly used as a tool to elicit stakeholder preferences; however, their implementation in oncology may be challenging if burdensome trade-offs (e.g. length of life versus quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 139 publications
(218 reference statements)
1
10
0
Order By: Relevance
“…We supplemented the database search by examining the references of the included articles. We also compared with the past reviews to confirm that we did not miss any studies [24,25]. The search strategy and results are presented in Supplementary Materials Section A.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…We supplemented the database search by examining the references of the included articles. We also compared with the past reviews to confirm that we did not miss any studies [24,25]. The search strategy and results are presented in Supplementary Materials Section A.…”
Section: Literature Searchmentioning
confidence: 99%
“…To better understand patient preferences toward targeted therapy for cancers, there is a need to systematically review DCE studies on this topic. Some previous reviews have summarized patient preferences for cancer treatments for specific cancers [17][18][19][20][21][22][23], and two studies synthesized evidence for multiple cancers [24,25]. Despite these efforts, the published reviews either focused on treating a specific type of cancer or did not use the DCE results to derive patients' WTP for cancer treatments, which would inform the clinical decisions and pharmaceutical regulations.…”
Section: Key Points For Decision Makersmentioning
confidence: 99%
“…Our research is also unique in that it is among the few studies to systematically assess the relative importance of treatment administration attributes (ie, mode and frequency of administration and number and duration of visits). For instance, Collacott et al reported on nine DCE studies in hematologic cancer 50 ; treatment administration attributes were considered in only three of these studies. 51 , 52 , 53 Therefore, our study adds to the understanding of the relative importance of treatment administration attributes.…”
Section: Hesitancy or [Feel] Guilty About Asking Questions Or Seeking...mentioning
confidence: 99%
“…Indeed, much of the health preferences literature in the MRS setting to date focus more on the broader aspects of cancer care and treatment modality preferences (for example, surgery, radiation therapy or active surveillance for prostate cancer treatment), 34 and very little preference literature around medical imaging. More broadly, there are few systematic literature reviews on preferences for cancer treatments 35,36 . A more detailed summary of methodological and outcome aspects for each of the example studies we are highlighting is provided in Table 2.…”
Section: Whose Preferences To Consider?mentioning
confidence: 99%
“…More broadly, there are few systematic literature reviews on preferences for cancer treatments. 35,36 A more detailed summary of methodological and outcome aspects for each of the example studies we are highlighting is provided in Table 2.…”
Section: Examples Of Dces From the Literaturementioning
confidence: 99%